Argentina : First Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance and Applicability of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
Argentina's First Review Under the Stand-By Arrangement and a Request for Waiver of Nonobservance and Applicability of Performance Criteria are reviewed. Favorable conditions allowed a further strengthening of the external position, though external arrears continued to increase. Congress has approved all the components of the government's anti-tax evasion package, including the tightening of rules on invoicing by commodity exporters, providing tax tribunals in Buenos Aires with federal jurisdiction, and introducing new penalties to reduce tax evasion.